2022
DOI: 10.3390/en15207749
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Feedstock in a Small-Scale Agricultural Biogas Plant

Abstract: Although no legal sustainability criteria have been formulated for electricity and heat production from biogas, the sustainability and profitability of large-scale biogas plants which use mainly energy crops is now questioned. Small (farm-size) biogas plants characterized by CHP electrical output in the range between 15 kWel and 99 kWel, operating on agricultural wastes and by-products, seem more suitable; however, the variety of feedstock may be crucial in the proper design and operation of such family biogas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, some national studies have shown that both the lack of subsidies and the decrease in revenues (sometimes by as little as 20%) or the necessary change in substrates may make the investment unprofitable [129]. In the case of this study, such a negative factor could be the introduction of a fee for emissions and their payment, or the need to change substrates, which may contribute to significant operational (and thus financial) problems [130].…”
Section: Discussionmentioning
confidence: 79%
“…However, some national studies have shown that both the lack of subsidies and the decrease in revenues (sometimes by as little as 20%) or the necessary change in substrates may make the investment unprofitable [129]. In the case of this study, such a negative factor could be the introduction of a fee for emissions and their payment, or the need to change substrates, which may contribute to significant operational (and thus financial) problems [130].…”
Section: Discussionmentioning
confidence: 79%
“…By the end of 2019, 9527 biogas plants had been developed in Germany [33]. However, the eco-friendliness of energy crops, the second most utilized feedstock in European biogas plants, for biogas production is questioned because of the impact on soil fertility and food production [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reasons for this situation, including low biogas efficiency with a minor degree of organic degradation, mainly due to the high water and fiber content [14,[48][49][50], the need to build large-capacity sealed tanks to store the resulting digestate [39], and lack of a sufficiently large and well-balanced (carbon to nitrogen ratio, organic or lignocellulose content, humidity, etc.) resource of substrates for year-round protection of the biogas plant feedstock [51][52][53][54]. The abovementioned aspects contribute to the insignificant profitability of investments in biogas plants.…”
Section: Introductionmentioning
confidence: 99%